Vo2 Max Level For Female Futsal Athletes WKB Pekanbaru - Ahmad Fazal Muttaqin; Oki Candra; Toktong Parulian (CV. AFDIFAL MAJU BERKAH, 2024)
The aim of this research was to see the VO2Max level of WKB Pekanbaru Female Athletes. Based on the results of observations made on women's futsal athletes at WKB Pekanbaru, several problems were found, including when shooting, the players were not hard enough to do it, they were less agile and when passing the ball to a friend they were less precise, and the athlete's discipline was still lacking in following the training process. ongoing so that it becomes an inhibiting factor. The test used in this research was the bleep test . The sample in this study was 15 female futsal athletes from WKB Pekanbaru. From the results of tests carried out on WKB Pekanbaru female futsal athletes, results were obtained in the